The dynamics of government bond yields in the Eurozone - Tanweer Akram; Anupam Das (Levy Economics Institute of Bard College, 2017)
This paper investigates the determinants of nominal yields of government bonds in the eurozone. The pooled mean group (PMG) technique of cointegration is applied on both monthly and quarterly datasets to examine the major drivers of nominal yields of long-term government bonds in a set of 11 eurozone countries. Furthermore, autoregressive distributive lag (ARDL) methods are used to address the same question for individual countries. The results show that short-term interest rates are the most important determinants of long-term government bonds' nominal yields, which supports Keynes's (1930) view that short-term interest rates and other monetary policy measures have a decisive influence on long-term interest rates on government bonds.
Keywords: E43; E50; E60; G10; G12; O16; 330; Government Bond Yields; Interest Rates; Monetary Policy; Eurozone